A randomized controlled trial of pretransplant antiviral therapy to prevent recurrence of hepatitis C after liver transplantation. Issue 5 (17th January 2013) - Everson, Gregory T.; Terrault, Norah A.; Lok, Anna S.; Rodrigo, Del R.; Brown, Robert S.; Saab, Sammy; Shiffman, Mitchell L.; Al‐Osaimi, Abdullah M.S.; Kulik, Laura M.; Gillespie, Brenda W.; Everhart, James E.; ,
Abstract: Hepatitis C virus (HCV) infection recurs in liver recipients who are viremic at transplantation. We conducted a randomized, controlled trial to test the efficacy and safety of pretransplant pegylated interferon alpha‐2b plus ribavirin (Peg‐IFN‐α2b/RBV) for prevention of post‐transplant HCV recurrence. Enrollees had HCV and were listed for liver transplantation, with either potential living donors or Model for End‐Stage Liver Disease upgrade for hepatocellular carcinoma. Patients with HCV genotypes (G) 1/4/6 (n = 44/2/1) were randomized 2:1 to treatment (n = 31) or untreated control (n = 16); HCV G2/3 (n=32) were assigned to treatment. Overall, 59 were treated and 20 were not. Peg‐IFN‐α2b, starting at 0.75 μg/kg/week, and RBV, starting at 600 mg/day, were escalated as tolerated. Patients assigned to treatment versus control had similar baseline characteristics. Combined virologic response (CVR) included pretransplant sustained virologic response and post‐transplant virologic response (pTVR), defined as undetectable HCV RNA 12 weeks after end of treatment or transplant, respectively. In intent‐to‐treat analyses, 12 (19%) assigned to treatment and 1 (6%) assigned to control achieved CVR ( P = 0.29); per‐protocol values were 13 (22%) and 0 (0%) ( P = 0.03). Among treated G1/4/6 patients, 23 of 30 received transplant, of whom 22% had pTVR; among treated G2/3 patients 21 of 29 received transplant, of whom 29% had pTVR. pTVR was 0%, 18%, and 50% in patients treated for <8, 8‐16, and >16 weeks, respectively ( P = 0.01). Serious adverse events (SAEs) occurred with similar frequency in treated versus untreated patients (68% versus 55%; P = 0.30), but the number of SAEs per patient was higher in the treated group (2.7 versus 1.3; P = 0.003). Conclusion : Pretransplant treatment with Peg‐IFN‐α2b/RBV prevents post‐transplant recurrence of HCV in selected patients. Efficacy is higher with >16 weeks of treatment, but treatment is associated with increased risk of potentially serious complications. (HEPATOLOGY 2013)